Inflammatory Myofibroblastic Tumor of the Orbit in an 8-Month Old. Issue 3 (May 2020) - Dermarkarian, Christopher R.; Patel, Kalyani R.; Fuller, Maren Y.; Bernini, Juan Carlos; Chévez-Barrios, Patricia; Allen, Richard C.
Abstract : Inflammatory myofibroblastic tumor is a mesenchymal neoplasm, commonly seen in the lung and abdominopelvic region of children. The authors present an 8-month-old female with a 2-month history of left-sided proptosis. Examination was significant for left-sided proptosis, a left exotropia and hypotropia, left supraduction and adduction deficits, and left optic disc elevation. MRI imaging revealed an extraconal left superomedial orbital mass with globe displacement and proptosis. Left anterior orbitotomy with excisional biopsy showed a solid mass composed of an infiltrative proliferation of bland spindle cells in a variably myxoid background with associated perivascular lymphoplasmacytic infiltration. Immunohistochemistry was positive for ALK-1 and CD34 and demonstrated focal positivity for S100. Fluorescence in-situ hybridization showed an additional copy of the 3′ALK gene (46%) in interphase cells examined. Next generation targeted sequencing found a DCTN1/ALK fusion. Findings were consistent with inflammatory myofibroblastic tumor. To the authors′ knowledge, this is one of the largest primary orbital inflammatory myofibroblastic tumors in the youngest reported patient. Abstract : Precis: We present an 8-month old with a unique presentation of orbital inflammatory myofibroblastic tumor. To our knowledge, this is the one of the largest and one of the youngest cases of orbital inflammatory myofibroblastic tumor reported.